Case Study On Three Five Systems, Inc - Palanisamy, Shanmuganathan (2004)
The report is to study the strategies and challenges of Three-Five Systems, Inc from its transformation as a unique expertise in display into a multi -dimensional company with broad manufacturing capabilities by its acquisition strategies of EMS companies.